Cerebrovascular Pressure Reactivity in Children with TBI - Laurence Ducharme-Crevier (Pediatric Neurology Briefs Publishers, 2015)
Investigators from University of Melbourne, Australia, studied Pressure-Reactivity Index (PRx) and optimal Cerebral Perfusion Pressure (CPP) in 36 children aged between 6 months and 16 years treated for traumatic brain injury (TBI) at the Royal Children's Hospital, Melbourne, from 2007 to 2013.